JFLAP SEBAGAI ALAT BANTU PENGAJARAN AUTOMATA - Zubair, Anis (Universitas Merdeka Malang, 2015)
Automata is a plural form of automaton. Automaton means machine, so automata means machines. There are many kinds of automata. Automata which we discuss in this paper is DFA, NFA, CFG, and PDA. We give each of them definition, example, accepted or rejected strings, and process Â about how to accept string visually in JFLAP